SOCIAL MEDIA AS MODERN PLATFORM TO CREATE AWARENESS OF SONOBUDOYO AND SANDI MUSEUMS IN YOGYAKARTA INDONESIA (Proceedings of the International Conference on Hospitality and Tourism Management, 2022)
Museum awareness through social media has been developing gradually. A previous study related to the topic found that museum social media was not well managed. It was related to the human resources competence in social media management even now it is defeated by better solution to have consultant or outsourcing. Good museum management will certainly have positive impact on the number of visits. However, not all museums have enough number of human resources and also have clear procedures for the use of related social media to increase the number of visits. The general objective of this study is to describe the maximum use of social media in order to increase the number of museum visits in Yogyakarta that specifically focuses on the types of social media and the strategies used to build awareness and interest in visiting the museum. The research method is a mixed qualitative quantitative approach in Sonobudoyo and Sandi museums in Yogyakarta, Indonesia as both museums have active social media. The respondents were thirty-nine Instagram followers of Sonobudoyo and thirty-eight followers of Sandi's Instagram. This study concludes that the two museums have good implementation of Social Media Marketing through Instagram and there is an increase in the number of visits after the social media used and entertainment content are well managed as the best strategy. It is suggested that the result of this study can provide solutions and input for other museums in Indonesia to become the preferred tourism destination to develop social media through the right Social Media Marketing (SMM) strategy to attract attention and interest of visitors, especially young people as the targets set by the government.
Keywords: social media; instagram; museum; marketing communication